Real‐life experience with inotersen in hereditary transthyretin amyloidosis with late‐onset phenotype: Data from an early‐access program in Italy. (28th March 2022) - Luigetti, Marco; Antonini, Giovanni; Di Paolantonio, Andrea; Gentile, Luca; Grandis, Marina; Leonardi, Luca; Lozza, Alessandro; Manganelli, Fiore; Mazzeo, Anna; Mussinelli, Roberta; My, Filomena; Obici, Laura; et al.
Abstract: Background and purpose: Hereditary transthyretin (TTR) amyloidosis (ATTRv) is a dominantly inherited, adult‐onset, progressive, and fatal disease caused by mutations in the transthyretin gene. Therapeutic agents approved for this disease include the TTR stabilizer tafamidis and the gene‐silencing drugs patisiran and inotersen. Inotersen is an antisense oligonucleotide that suppresses the hepatic production of transthyretin. After European Medical Agency approval in 2018, an early‐access program was opened in Italy, and in this article, we present the long‐term outcome of a cohort of Italian ATTRv patients who received inotersen within this program. Methods: This is a multicenter, observational, retrospective study of patients affected by ATTRv that started inotersen during the early‐access program. The primary end point was safety. Secondary end points included change from baseline in familial amyloid polyneuropathy (FAP) stage, Polyneuropathy Disability, Neuropathy Impairment Scale, Compound Autonomic Dysfunction Test, Norfolk Quality of Life–Diabetic Neuropathy, troponin, N‐terminal pro–brain natriuretic peptide, interventricular septum thickness, and body mass index. Results: In total, 23 patients were enrolled. No patient permanently discontinued the treatment because of thrombocytopenia, and no cases of severe thrombocytopenia were observed. Five patients discontinued the treatment permanently because of voluntary withdrawal (two patients), renal failure after infective pyelonephritis, not related to inotersen, drug‐related hypotension, and amyloid‐negative crescentic glomerulonephritis. In seven patients, dosing frequency was reduced to every 2 weeks due to recurrent thrombocytopenia. Considering the FAP stage, only two patients worsened, whereas the other 21 patients remained stable until the last follow‐up available. Conclusions: The long‐term safety profile of inotersen is favorable. Neurologic disease severity at baseline is the main factor associated with progression. Abstract : Patients' enrollment and familial amyloid polyneuropathy (FAP) stage and Polyneuropathy Disability (PND) score change across the study. FAP stage overall remained stable in 91.3% of patients. PND score was unchanged in 78.3% and improved in 4.3% of the patients.